Determining the Root Causes of Complications in Hemodialysis Maintenance Therapy - Ibtisam Nazi Khan; Pankaj Kaul (Emerging Trends in Metabolites, 2024)
As with peritoneal dialysis and kidney transplantation, hemodialysis has been considered one of the most effective therapies for the replacement of kidney function. While this helps to save patients with the disease by decreasing morbidity /mortality/ rates, this medication has some side effects. These may manifest during the dialysis process alongside the ongoing treatment. Avoiding these barriers becomes crucial for improving the patients’ prognosis in this context.We are going to mention some short-term complications temporarily observable during sessions, such as muscle cramps or hypotension, or more related to the middle-long term, for instance, vascular access issues or electrolyte disorders. Hypotesnion, muscle cramps, hypoglycemia, electrolyte disturbances, disequilibrium syndrome, hypocalcemia, etc. are common complications occur during dialysis. In the extended course of dialysis treatment, patients often contend with complications such as bone disease, disruptions in endocrine function, infections, and cardiovascular issues. These challenges underscore the significance of ongoing vigilance and tailored care to manage the diverse health needs of individuals undergoing chronic hemodialysis. Hemodialysis is a crucial renal replacement therapy, alongside peritoneal dialysis and renal transplantation, utilized to manage end-stage renal disease (ESRD) by filtering waste products and excess fluids from the blood. Despite its efficacy in improving morbidity and mortality rates among renal patients, hemodialysis is associated with a variety of complications that can arise both during the dialysis sessions and with long-term use. Acute complications during dialysis sessions include hypotension, which is the most common and often results from rapid fluid removal. Muscle cramps can occur due to shifts in fluid and electrolyte balances. Hypoglycemia is another potential issue, particularly in diabetic patients, due to the glucose-free dialysate used during treatment. Electrolyte imbalances, such as hyperkalemia or hypokalemia, can also develop, requiring vigilant monitoring of serum levels to ensure proper management. Additionally, dialysis disequilibrium syndrome, characterized by neurological symptoms due to rapid changes in blood solute levels, and hypocalcemia, resulting from calcium removal during dialysis, are notable acute complications. Long-term hemodialysis use can lead to more chronic complications, significantly impacting patient quality of life. Bone disease, or renal osteodystrophy, is prevalent due to disrupted calcium and phosphate metabolism. Endocrine disturbances, such as altered thyroid function and sexual dysfunction, are also common. Sepsis could arise from infection, especially at the site of the vascular access line, where it poses a great risk. In addition, longer-term dialysis patients are also predisposed to hypertension, left ventricular hypertrophy, and other cardiovascular complications, which are the leading causes of death for chronic dialysis patients. These complications make it evident that there exist significant gaps where integrated approaches need to be implemented to address all the risks that patients undergoing hemodialysis face.
Keywords: Infection; hemodialysis; hemodialysis complications; hypotension; muscle cramps